Cortical inexcitability defines an adverse clinical profile in amyotrophic lateral sclerosis. (9th October 2020) - Dharmadasa, T.; Howells, J.; Matamala, J. M.; Simon, N. G.; Burke, D.; Vucic, S.; Kiernan, M. C.
Abstract : Background and purpose: In amyotrophic lateral sclerosis, studies using threshold‐tracking transcranial magnetic stimulation (TMS) have identified corticomotoneuronal dysfunction as a key pathogenic mechanism. Some patients, however, display no motor response at maximal TMS intensities, termed here an 'inexcitable' motor cortex. The extent to which this cortical difference impacts clinical outcomes remains unclear. The aim of this study was to determine the clinical profile of patients with inexcitability to TMS. Methods: Motor cortex excitability was evaluated using TMS. Patients in whom a motor evoked potential could not be recorded in one or more limbs at maximal TMS intensities were classified as four‐limb or partially inexcitable. Demographic information, clinical variables and survival data were analysed. Results: From 133 patients, 40 were identified with inexcitability. Patients with four‐limb inexcitability were younger ( P = 0.03) and had lower‐limb disease onset (64%), greater functional disability ( P < 0.001) and faster disease progression ( P = 0.02), particularly if inexcitability developed within 1 year of symptoms ( P < 0.01). Patients with partial inexcitability had higher resting motor thresholds compared to the excitable cohort ( P < 0.01), but averaged short‐interval intracortical inhibition was similar ( P = 0.5). Mean survival was reduced if inexcitability involved all limbs within 12 months of symptom onset ( P = 0.04). Conclusion: Amyotrophic lateral sclerosis patients with inexcitability of all four limbs to TMS have a distinct clinical profile of younger age and lower‐limb onset. Importantly, these patients display a more malignant disease trajectory, with faster progression, greater functional disability and reduced survival when occurring in early disease. This measure may provide an important prognostic marker in amyotrophic lateral sclerosis. Abstract : Patients with amyotophic lateral sclerosis who display 'cortical inexcitability' to transcranial magnetic stimulation in all four limbs have a unique clinical profile and are defined by an adverse disease trajectory, with reduced survival if present early in disease